Potential for Hungarian Grasslands in integrated rural development - Nagy, Géza (Applied Studies in Agribusiness and Commerce, 2009)
Sustainability and multifunctionality, two key principles, which will determine future development in any activities. On the bases of these principles, society as a whole has already outlined future expectations towards rural areas. Rural functions (economic, ecological and socio-cultural ones) have been declared in European Charter for RuralAreas. To what extend can different rural development initiatives meet these functions? The question may be answered by using the method of multifunctional rural resource analysis (NAGY, 2007). The paper is investigating the potential for Hungarian grasslands by using this methodology. It is concluded that our grasslands, as land use systems in their present conditions can participate in integrated rural development in the most balanced way compared to other land use systems in the county. Economically their potential is good. Ecologically their potential is outstanding. The socio-cultural potential of grassland use in Hungary is also outstanding due to the historical roots.As a future prediction the relative importance of the three grassland functions has been outlined in integrated agriculture and rural development.